Majlis Pengajian Ilmu Tauhid Tasawuf "Ushuluddin" : laporan studi kasus keagamaan - Asry, H. M. Yusuf (Badan Penelitian dan Pengembangan Agama, Departemen Agama RI, 1989)
Background history and teachings of Majlis Pengajian Ilmu Tauhid Tasawuf Ushuluddin, an Islamic group in Banjarmasin, Kalimantan Selatan Province; case study.